RANCANG BANGUN MESIN FILLING DAN PRESSING MEDIA TANAM JAMUR UKURAN 18 CM X 35 CM DENGAN BERAT 1,3 KG SAMPAI DENGAN 1,4 KG - Dwiky Setiawan Putra Wardana; Pranowo Sidi; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
One of the strategies to accelerate economic in facing global competition is to improve the development through community empowerment efforts in various fields of life through the implementation of appropriate technology. The oyster mushroom cultivation food industry sector also got the influence of technology. The use of technology in the food industry is one of the solution to meet the needs of oyster mushrooms in society. Therefore a machine is needed that can help the process of cultivating mushrooms, of which are still in the micro and small business category. Filling and pressing machines for mushroom growing media are expected to accelerate and increase the productivity of farmers. The production speed and worker effectiveness can be increased through two work processes in one machine. Integrated design method is used in designing and manufacturing the machine. The selection of the AC motor driving concept and only using the mechanical motion of the screw conveyor to fill and the crank slider to compact the planting media on the machine aims to avoid damaging the composition of the mixture. With the design of filling and pressing machines, it is expected that the mushroom growing media can meet the standard criteria for planting media, namely a height of between 21 to 22 centimeters and weighing between 1.3 to 1.4 kilograms.